Comparison of molecular adsorption ability of the molecularly imprinted polymers prepared by ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate as cross linkers - Zikant Saenkasa (2018)
The target of this study was to synthesize the molecularly imprinted polymers (MIPs) of L-phenylalanine as the solid phases for characterization of molecular adsorption by molecularly imprinted solid phase extraction (MISPE). These MIPs, in microscale, were synthesized using thermal (40°C)-compared with thermal (65°C)-initiated polymerization process. Itaconic acid was chosen as the functional monomers, and either ethylene glycol dimethacrylate or trimethylolpropane trimethacrylate (TRIM) was used as the cross linker and was compared together. The influences of several parameters on the properties of the MIPs were investigated, especially physical robustness from the percentage yields and molecular adsorption from the percentage recovery by MISPE. The best yields were obtained from polymers made using TRIM and thermal (65°C)-initiated polymerization. However, there were no significant differences in molecular adsorption. It was concluded that these parameters can be considered to synthesize MIPs for chiral separation in advance steps such as other related Chromatographic techniques. © 2006 Wiley Periodicals, Inc.